Kinanthropometry and performance of elite triathletes - Landers, G.; Blanksby, B. A.; Ackland, T. R.; Smith, D. (1999)
The need to investigate the morphology of triathletes and its relationship with performance was deemed necessary after triathlon was accepted into the Olympic programme in Sydney 2000. The event consisting of 1.5 km swim, 40 km cycle, 10 km run and two transitions, takes approximately 1 h 50 min for elite male and 2 h for elite female triathletes to complete. Seventy one triathletes from 11 nations competing in the elite or junior elite categories at the 1997 World Triathlon Championships were measured on a battery of 28 anthropometric dimensions. After landmarking by a criterion anthropometrist, each triathlete was directed to one of five stations for the measurement of eight skinfolds, seven direct lengths, seven segment girths, five segmental breadths plus body mass. A factor analysis was performed to reduce the number of independent variables prior to their entry into a step-wise linear regression analysis. The four factors revealed were; robustness, adiposity, segmental lengths and skeletal mass. Significant (p<0.05) regression equations were developed for males, females and all triathletes based on component and complete triathlon times. Relating these factors to the total time obtained by the triathletes in this study yielded a regression equation that accounted for 47 percent of the variance in total triathlon duration. The regression equations indicated the importance of low levels of adiposity, with weights of 324.8, 195.6 and 233.1 for all triathletes, male triathletes and female triathletes respectively. This was borne out for total time and most of the subdisciplines. The other factor which showed importance was that proportionally longer segmental lengths contributed to successful swimming outcome.